2017
DOI: 10.29252/hmj.21.4.271
|View full text |Cite
|
Sign up to set email alerts
|

Spirometry pattern and respiratory symptoms in sweepers

Abstract: Introduction: Multiple and sometimes contradictory evidence exists on the relationship between dust exposure and respiratory symptoms with pulmonary disorders. The study was conducted to examine the effects of chronic exposure to street dust on the pulmonary parameters and respiratory complaints in sweepers. Methods: This cross-sectional study was conducted on 100 sweepers working in district 3 Bandar Abbas municipality in 2014. The control group was selected from the staff of the same municipality with an off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Other authors also reported a negative correlation between the duration of exposure and lung function values for street sweepers [12,[27][28][29]. In most of the recent studies, the results of lung function measurements were adjusted for smoking [24,28] or the comparison with control subjects was only performed in non-smoking subjects [23,25,29]. Most of these studies showed that the decline of lung function was aggravated in smoking individuals.…”
Section: Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors also reported a negative correlation between the duration of exposure and lung function values for street sweepers [12,[27][28][29]. In most of the recent studies, the results of lung function measurements were adjusted for smoking [24,28] or the comparison with control subjects was only performed in non-smoking subjects [23,25,29]. Most of these studies showed that the decline of lung function was aggravated in smoking individuals.…”
Section: Infectionsmentioning
confidence: 99%
“…A number of studies have revealed that street sweepers, especially in emerging and developing countries, are at risk of infectious diseases as they are exposed to inhalable matter, microorganisms, injuries, cuts and wounds. While a Kenyan study found that the involved street cleaners had little knowledge about the possible ways of transmitting infections and diseases [13], interviews with 70 street sweepers and garbage collectors from Egypt showed that between street cleaners and control subjects [23][24][25], indicating an obstructive pattern. Additionally, Sani et al [24] discussed that, due to the significant decline in forced expiratory flow (FEF 25-75 ) and peak expiratory flow (PEF), dust exposure of street sweepers might cause obstructive changes also in the small airways.…”
Section: Infectionsmentioning
confidence: 99%
See 1 more Smart Citation